Effect of weed management practices on cowpea production - Oliveira, Kelder José Alves de; Pessôa, Uriel Calisto Moura; Souza, Anielson dos Santos; Pimenta, Thiago Alves; Muniz, Rafael Vitor da Silveira; Araújo Neto, Antônio Gomes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The cowpea stands out among the annual crops in the Northeast region for its productive potential and nutritional value. However, it has been showing productivity below its true productive potential, due to the severe interference of the weed community, which can lead to a reduction in grain yield of up to 90%. The objective of this study was to evaluate the effect of different weed management on cowpea and to identify the most efficient crop production components. The work was carried out in the Center of Sciences and Technology Agroalimentar of the Federal University of Campina Grande, Campus Pombal. The experimental design was a randomized block design in a 4 x 2 factorial scheme, with two cultivars (BRS Marataoã and BRS Rouxinol) and four weeds (mechanical, chemical, physical and uncontrolled) with four replications. The production components were: Mass (kg) of the pods, number of grains per pod, size (cm) and diameter (mm) of the pods, Mass (kg) of one thousand seeds and total grain yield (kg). There was a drastic reduction in the productivity of the plants cultivated in the treatment without control, independent of the cultivar.